PERSEPSI DAN SIKAP WISATAWAN MILENIAL TERHADAP PARIWISATA DI ERA COVID 19 - I Gusti Agung Febrianto (JURNAL KEPARIWISATAAN, 2021)
The tourism sector has been predicted as the second largest source of foreign exchange contribution in Indonesia, but the Covid-19 pandemic has made this sector sluggish. The government is making various efforts so that the tourism sector can return to normal. The millennial generation relatively bolder when traveling when compared to the previous generation. With the opening of tourism era of covid 19, the millennial generation will immediately carry out travel activities. The purpose of this study is to determine the perceptions and attitudes of millennial tourists towards tourism era of covid 19. The perception of millennial generation tourists focuses on risks when traveling. Attitude is an evacuation of belief in positive feelings or negative feelings from someone if they have to perform a behavior that will determine. The number of respondents in this study were 100 tourists. The method used is descriptive quantitative. The result of this study is that millennial tourists' perceptions of tourism in the new normal era prioritize the quality of health protocols both in hotels, restaurants, transportation, and in tourist attractions. Likewise, the attitude of millennial tourists towards tourism in the new normal era is more concerned about safety, health and cleanliness when traveling.